Urban Sprawl Analysis in Jalingo Metropolis, Taraba State Nigeria - K, Garboa; E.D, Oruonye; Y.M, Ahmed (Review of Environment and Earth Sciences, 2016)
This study analyzed spatial and temporal land use /land cover change in Jalingo Metropolis, Taraba State, north east Nigeria. This was carried out with the use of land sat images from 1990-2015. Satellite images were obtained from the United State Geological Survey (USGS) database online resources. The images were georeferenced and processed. Supervised image classification technique was employed. Ground truthing field survey was carried out to complement information about the types of land use and land-cover classes in the area. The change detection and change matrixes of the classified satellite images were analyzed using percentage to see the rate of change in a simple form. Land use maps were obtained through supervised classifications of satellite imageries and presented in Tables. The findings of the study show that Jalingo Metropolis has witnessed unprecedented spatial growth over the years. The town has grown from 6.01km2 in 1990 to 55.7km2 in 2005 and 101.16 in 2015. This growth was as a result of change in the status of the metropolis from Local Government headquarters to state capital which brought about the establishment of government ministries and agencies, with wide range of opportunities. Despite the existence of master plan, implementation has not been satisfactory for a number of reasons. This has resulted in proliferation of haphazard and uncontrolled development (including slums and squatters), environmental degradation, lack of basic amenities and transportation problems within and around the town. The study recommends the need to update the urban database of Jalingo town using GIS and Remote Sensing techniques to plan and monitor urban land use changes in the area.